Indonesian PENERAPAN PENDEKATAN KONSTRUKSIVISME DALAM MENGOPTIMALKAN KEMAMPUAN BERPIKIR KRITIS PADA PEMBELAJARAN IPAS SISWA MADRASAH IBTIDAIYAH - Cahyaningsih, Esty; Maemonah (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2024)
This research investigates the application of the constructivist approach in enhancing critical thinking skills in science learning. The subjects of this study include the principal, the 5B class teacher, and 30 students from class 5B at MIN 2 Bantul. The researchers employed a constructivist philosophical approach with a case study design. Data sources consisted of interviews, observations, documentation, and analysis of additional supporting documents. After data collection and aggregation, the data were analyzed using the interactive model by Miles, Huberman, and Saldana, which includes data condensation, data display, and conclusion drawing or verification. To ensure data validity, data triangulation was employed. The findings of this research indicate that utilizing a constructivist approach in science education enhances student engagement, fosters enthusiasm, and optimizes critical thinking skills in addressing learning challenges